2005
DOI: 10.1097/01.mpg.0000162479.74277.86
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Clinical Presentation and Location at Diagnosis of Pediatric Inflammatory Bowel Disease: A Prospective Population‐Based Study in Northern France (1988‐1999)

Abstract: The incidence of Crohn disease in the children of northern France showed an increasing trend (20%; not significant) during the 12-year period while the incidence of ulcerative colitis remained stable. In the entire population(children and adults)the incidence of Crohn disease increased significantly (+23%; P < 0.001), while the incidence of ulcerative colitis decreased (-17%; P < 0.0001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
126
4
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(158 citation statements)
references
References 18 publications
(56 reference statements)
17
126
4
11
Order By: Relevance
“…The incidence in CD rose from 1.5/10 5 to 8.4/10 5 (mainly in the age group of 10-15 years), while that of UC was relatively stable at approximately 1.8-1.9/10 5 , except for 1990-1992. One of the largest studies has been reported from Northern France [43] . In a prospective follow-up study, a total of 7066 patients were diagnosed, 509 (7.2%) of them were under the age of 17 years at the time of diagnosis.…”
Section: Most Of the Published Data Come From The Unitedmentioning
confidence: 99%
“…The incidence in CD rose from 1.5/10 5 to 8.4/10 5 (mainly in the age group of 10-15 years), while that of UC was relatively stable at approximately 1.8-1.9/10 5 , except for 1990-1992. One of the largest studies has been reported from Northern France [43] . In a prospective follow-up study, a total of 7066 patients were diagnosed, 509 (7.2%) of them were under the age of 17 years at the time of diagnosis.…”
Section: Most Of the Published Data Come From The Unitedmentioning
confidence: 99%
“…A European study reported that in the entire IBD population (children and adults) the incidence of Crohn's disease (CD) increased significantly (+23%), while the incidence of ulcerative colitis (UC) decreased (-17%) [1] . One of the best North American studies reported the incidence of IBD in Wisconsin children to be 7.05 per 100 000, with the incidence for Crohn's disease being ������ ��������� ������ ��������� 4.56, more than twice the rate of ulcerative colitis (2.14).…”
Section: Introductionmentioning
confidence: 99%
“…Budući da podatci svjetske literature govore u prilog trendu porasta incidencije kroničnih upalnih bolesti crijeva u djece, prvenstveno na račun Crohnove bolesti, ne čudi činjenica da je najčešće proučavan parametar baš incidencija bolesti, (10,11,16,17,21,22,(37)(38)(39). Najviši porast ukupne incidencije zabilježen je u Španjolskoj -u posljednjih 30-ak godina čak šesnaesterostruk (21,39).…”
Section: Incidencijaunclassified
“…Najviši porast ukupne incidencije zabilježen je u Španjolskoj -u posljednjih 30-ak godina čak šesnaesterostruk (21,39). Iako je prema literaturi uglavnom zabilježen veći porast incidencije Crohnove bolesti (10,17,21,22,38,39), podatci nisu konzistentni; npr. Italija bilježi značajan porast ulceroznog kolitisa (11).…”
Section: Incidencijaunclassified